Increased prevalence of sleep disturbance in psoriatic arthritis is associated with inflammatory and non-inflammatory measures. (4th May 2023) - Skougaard, M; Stisen, ZR; Jørgensen, TS; Egeberg, A; Hansen, RL; Perez-Chada, LM; Mogensen, M; Merola, JF; Gerwien, JG; Kristensen, LE
Abstract : Objectives: To examine the prevalence of sleep disturbances, quantified by the Pittsburgh Sleep Quality Index (PSQI), in patients with psoriatic arthritis (PsA), psoriasis (PsO) and healthy controls (HCs), explore associations between PSQI and clinical and patient-reported outcomes, and evaluate the effect of treatment on PSQI. Method: Patients were included from the Parker Institute's PsA patient cohort to evaluate the prevalence of sleep disturbances. Univariate and multivariate regression analyses were used to explore associations between sleep disturbance and outcome measures. Treatment effect in PsA patients was assessed with a mixed-effect model for repeated measures. Results: In total, 109 PsA patients, 20 PsO patients, and 20 HCs were included. Sleep disturbances were reported by 66.1% of PsA patients, 45.0% of PsO patients, and 15.0% of HCs. Univariate regression analyses revealed statistically significant associations (p < 0.001) between PSQI and Disease Activity Score (DAS28CRP), tender points, visual analogue scale (VAS) patient global and pain, Psoriatic Arthritis Impact of Disease fatigue, Health Assessment Questionnaire (HAQ), and painDETECT score. Multivariate regression analysis demonstrated VAS patient global, VAS pain, and tender points as being independently associated with PSQI. The mixed-effect model revealed no effect of treatment.                   Conclusion: More PsA patients than PsO patients and HCs reported sleep disturbances. Sleep disturbances were associated with inflammatory and non-inflammatory measures possibly explaining the limited effect of treatment. This demonstrates the need for interdisciplinary approaches to improve the management of sleep disturbance in PsA. Trial registration : ClinicalTrials.gov (NCT02572700)